Analisa Kualitas Layanan pada Laboratorium Praktek Tata Boga pada SMK Ibu Pertiwi 1 dengan Metode Servicequality - Muhammad Thoriq Alfakhri; Rouli Doharma (Universitas Maritim AMNI Semarang, 2024)
This study aims to analyze the quality of service in the Culinary Arts Practical Laboratory at SMK Ibu Pertiwi 1 using the Service Quality (Servqual) method. Service quality is an important element in supporting the success of the education process, especially in the Culinary Arts expertise program that requires laboratory facilities as a means of practical learning. The Servqual method is used to evaluate five main dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy.This study was conducted by collecting data through questionnaires distributed to students as users of laboratory services. Data analysis used a comparison between students' expectations of ideal service quality and their perceptions of the services received. The results of the study showed a gap in several dimensions of service quality, especially in the tangibles dimension which includes the completeness and condition of laboratory facilities. In addition, the responsiveness and reliability dimensions are also of concern because students feel that the response to complaints and service consistency are not optimal.From the results of the study, it can be concluded that the quality of laboratory services needs to be improved to meet student expectations. Recommendations for improvement include improving physical facilities, training for laboratory staff to improve responsiveness and reliability, and strengthening security assurance in the practical learning process. This study contributes to school management in creating a more effective and quality learning environment.